Grief, poetry, and the sweet unexpected. Issue 1 (2nd January 2018) - Gold, Richard; Jordan, Elizabeth
ABSTRACT: This paper explains the healing benefits, the "sweet unexpected" of the title, which results from using poetry to engage trauma, including traumatic grief. The benefits of poetry are presented alongside a discussion of a 22-year-old nonprofit called The Pongo Poetry Project. The sweet unexpected includes the ease with which trauma survivors engage their trauma narrative, the critical insights that emerge in poetry, the beneficial social context of sharing poetry, and the healing benefits of poetry for writers, care providers, and readers alike. The paper concludes by providing resources that can help people use poetry in their own work.